Indigenous Cinema in Brazil and Canada weaving cultures: Topawa (2020) and Waban-aki: People from Where the Sun Rises (2007) - Pinheiro, Neide Garcia (Ilha do Desterro A Journal of English Language, Literatures in English and Cultural Studies, 2022)
Based on a brief reflection on indigenous cinema, this article presents a comparative study between two productions, one Brazilian and the other Canadian. In the documentary Topawa (2020), a collective of Parakanã filmmakers from the Amazon region in Brazil presents the process of production of traditional hammocks. In Waban-aki: People from Where the Sun Rises (2007), Canadian filmmaker Alanis Obomsawin presents a lyrical portrait of her people, the Abenaki, in the contemporary struggle to keep traditional basketry alive. Even considering the differences in the production context of the two documentaries, both explore a common theme, the role of traditional activities in the complex process of (re)construction of cultural identity in the face of historical adversities. The two productions also illustrate that indigenous cinema goes beyond local borders to encompass a wider movement in the Americas and the world for indigenous political affirmation and cultural renaissance Partindo de uma breve exposição sobre o cinema indígena, este artigo aborda duas produções, uma brasileira e outra canadense. No documentário Topawa (2020) , um coletivo de cineastas do povo Parakanã, da região amazônica no Brasil, apresenta o trabalho de produção artesanal de redes. No documentário Waban-aki: People from Where the Sun Rises (2007), a cineasta canadense Alanis Obomsawin constrói um retrato lírico de seu povo, os Abenaki, na luta contemporânea para manter vivas as práticas tradicionais de cestaria. Ainda que se considerem as diferenças de contexto de produção dos dois documentários, ambos exploram um tema em comum, o papel das atividades tradicionais no complexo processo de (re)construção de identidade cultural em virtude de adversidades históricas. As duas produções ilustram que o cinema indígena ultrapassa as fronteiras locais, incluindo-se em um movimento nas Américas e no mundo para a afirmação política e renascença cultural indígena.